ASSESSMENT OF ECONOMIC DAMAGE CAUSED BY VARICELLA INFECTION ORIGINAL ARTICLE - E.M. Voronin; I.L. Shakhanina; I.V. Mikheeva; I.N. Litkina; N.N. Filatov ("Paediatrician" Publishers LLC, 2011)
Nowadays varicella infection is important to the public health specialists due to not only its high morbidity rates, but also the existence of severe forms that can lead to serious complications and even death. The overall damage caused by varicella infection and its' complications in the Russian Federation is a multicomponent and a multiple-factor figure, that reflects considerable annual economic damage caused by this infection. In this article one can find a substantiation of the suitability of varicella infection immunization on a national scale. Key words: varicella, economic damage due to infectious diseases. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 18-23.)